Factor XIII topology: organization of B subunits and changes with activation studied with single‐molecule atomic force microscopy. (14th March 2019) - Protopopova, Anna D.; Ramirez, Andrea; Klinov, Dmitry V.; Litvinov, Rustem I.; Weisel, John W.
Abstract : Essentials Factor XIII is a heterotetramer with 2 catalytic A subunits and 2 non‐catalytic B subunits. Structure of active and inactive factor XIII was studied with atomic force microscopy. Inactive factor XIII is made of an A2 globule and 2 flexible B subunits extending from it. Activated factor XIII separates into a B2 homodimer and 2 monomeric active A subunits. Summary: Background: Factor XIII (FXIII) is a precursor of the blood plasma transglutaminase (FXIIIa) that is generated by thrombin and Ca 2+ and covalently crosslinks fibrin to strengthen blood clots. Inactive plasma FXIII is a heterotetramer with two catalytic A subunits and two non‐catalytic B subunits. Inactive A subunits have been characterized crystallographically, whereas the atomic structure of the entire FXIII and B subunits is unknown and the oligomerization state of activated A subunits remains controversial. Objectives: Our goal was to characterize the (sub)molecular structure of inactive FXIII and changes upon activation. Methods: Plasma FXIII, non‐activated or activated with thrombin and Ca 2+, was studied by single‐molecule atomic force microscopy. Additionally, recombinant separate A and B subunits were visualized and compared with their conformations and dimensions in FXIII and FXIIIa. Results and Conclusions: We showed that heterotetrameric FXIII forms a globule composed of two catalytic A subunits with two flexible strands comprising individual non‐catalytic B subunits that protrude on one side of the globule. Each strand corresponds to seven to eight out of 10 tandem repeats building each B subunit, called sushi domains. The remainder were not seen, presumably because they were tightly bound to the globular A2 dimer. Some FXIII molecules had one or no visible strands, suggesting dissociation of the B subunits from the globular core. After activation of FXIII with thrombin and Ca 2+, B subunits dissociated and formed B2 homodimers, whereas the activated globular A subunits dissociated into monomers. These results characterize the molecular organization of FXIII and changes with activation.